The evolution of withdrawal: negotiating research relationships in biobanking - Melham, Karen; Moraia, Linda Briceno; Mitchell, Colin; Morrison, Michael; Teare, Harriet; Kaye, Jane (Life sciences, society and policy, 2014)
The right to withdraw from research, along with the necessity of adequately informed consent, is at the heart of the post-Nuremburg code of ethical safeguards in biomedical research on human participants. As biomedical research moves away from direct interventional studies towards research using networks of linked human tissue samples and data, however, questions arise about what withdrawal can and should mean in these new contexts. Some of the more expansive traditional understandings, such as the right to withdraw from a study `at any time' are limited in practice by the nature of biobank- supported research, particularly where it makes possible widespread dissemination and ongoing reuse of data. It is time for a more nuanced, granular arrangement for withdrawal, appropriate to the ongoing relationships between participants and long-term biobanking enterprises.